The cost‐effectiveness of patient‐controlled analgesia vs. standard care in patients presenting to the Emergency Department in pain, who are subsequently admitted to hospital. (26th May 2017) - Pritchard, C.; Smith, J. E.; Creanor, S.; Squire, R.; Barton, A.; Benger, J.; Cocking, L.; Ewings, P.; Rockett, M.; ,
Summary: The clinical effectiveness of patient‐controlled analgesia has been demonstrated in a variety of settings. However, patient‐controlled analgesia is rarely utilised in the Emergency Department. The aim of this study was to compare the cost‐effectiveness of patient‐controlled analgesia vs. standard care in participants admitted to hospital from the Emergency Department with pain due to traumatic injury or non‐traumatic abdominal pain. Pain scores were measured hourly for 12 h using a visual analogue scale. Cost‐effectiveness was measured as the additional cost per hour in moderate to severe pain avoided by using patient‐controlled analgesia rather than standard care (the incremental cost‐effectiveness ratio). Sampling variation was estimated using bootstrap methods and the effects of parameter uncertainty explored in a sensitivity analysis. The cost per hour in moderate or severe pain averted was estimated as £24.77 (€29.05, US30.80) (bootstrap estimated 95%CI £8.72 to £89.17) for participants suffering pain from traumatic injuries and £15.17 (€17.79, US18.86) (bootstrap estimate 95%CI £9.03 to £46.00) for participants with non‐traumatic abdominal pain. Overall costs were higher with patient‐controlled analgesia than standard care in both groups: pain from traumatic injuries incurred an additional £18.58 (€21.79 US23.10) (95%CI £15.81 to £21.35) per 12 h; and non‐traumatic abdominal pain an additional £20.18 (€23.67 US25.09) (95%CI £19.45 to £20.84) per 12 h.